Statement in Support of Diversity, Equity, and Inclusion for AGU GeoHealth Section - K. Ardon‐Dryer; F. Lo; U. Ovienmhada (GeoHealth, 2024)
Abstract This commentary presents the American Geophysical Union's GeoHealth section statement in support of diversity, equity, and inclusion (DEI). The GeoHealth section is an open community that represents diverse backgrounds in the geophysical, biological, and public health sciences that share a passion for research at the nexus of Earth and health sciences. The GeoHealth section will aim to advance our understanding of the interactions between the environment, human health, and well‐being while supporting DEI topics. The GeoHealth Section will ensure a strong and sustained focus on different DEI‐related issues by performing different activities presented in this commentary.